A survey on enhancement of power system performances by optimally placed DG in distribution networks - Bindeshwar Singh; Deependra Kumar Mishra (Energy Reports, 2018)
This paper presents a survey on enhancement of power system performances by optimally placed distributed generations in distribution networks. Thedistribution power system performances such as minimization of real power loss, minimization of reactive power loss, improvement of voltage profile, short circuit current capacity, system average interruption duration index (SAIDI), customers average interruption duration index (CAIDI), power system oscillations, available power transfer capacity of system, loadability of the system, reliability and security of the system, power system stability etc. are consider in this survey paper as major issue in distribution networks. Such power system performances can be enhance by conventional devices as well as planning of DG technologies such as fuel cell, biogas, wind turbine, photovoltaic, solar, geo-thermal, tidal and wave etc. This survey paper is very much useful for scientific persons, engineers, industrial persons and researchers regarding with enhancement of power system performances by optimally placed distributed generations in distribution networks.
Keywords: 330; Artificial intelligence techniques; Distributed generation (DG); Distribution networks (DNs); Optimally placed distributed generation; Power system performances